Efektifitas Program Palembang go-digital Bagi Pelaku UMKM Di Masa Pandemi Covid-19 - Dwi Mirani; Januar Eko Aryansah; Farisha Sestri Musdalifah (Kolaborasi : Jurnal Administrasi Publik, 2022)
This study aims to analyze the effectiveness of implementing the go-digital Palembang Program for MSME actors during the COVID-19 pandemic and the supporting and inhibiting factors for program implementation. The method used in this study is a qualitative descriptive method using interview, observation and documentation techniques. The results of the study show that this program has not been effective. Analysis of the supporting factors shows that this program provides convenience for business actors in marketing their products, so that support comes from business actors who are enthusiastic about this program, but from the results of the study it was also found that inhibiting factors were obstacles in its implementation, including lack of socialization, low mastery of technology. MSME actors, program budget reductions due to the pandemic, lack of implementing human resources, and lack of enthusiasm for consumer support for the digital media website used. The Palembang Go-Digital program as an effort to develop MSMEs during the Covid-19 pandemic needs to be evaluated because existing obstacles can become obstacles to increasing MSME businesses in developing and maintaining business sustainability.